Performance of mid-lactating dairy cows fed a grain sorghum-soybean silage base diet - H. Hartadi; L. Harbers; John E. Shirley; K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1991)
Whole-plant silage from intercropped grain sorghum and Williams 82 soybean was compared to corn silage in a mixed diet for mid-lactation dairy cows. Cows fed the grain sorghum-soybean silage yielded 45.13 lb and those fed corn silage yielded 44.05 lb of fat (4%)-corrected milk daily. Milk yield, milk fat, and milk lactose percentages were similar between cows fed the two silages. Protein and solids non-fat percentages for the cows fed the corn silage diet were .09 and .06 units greater than those of cows fed the grain sorghum silage. Cows fed the corn silage tended to gain more (+105.8 lb) than those fed the grain sorghum-soybean silage (+95.2 lb). We conclude that, if the cost for producing intercropped grain sorghum and soybean silage (ton/acre) is at least similar to that of producing corn silage, the intercropped grain sorghum and soybean silage can be substituted for corn silage in a mid-lactation dairy cow diet.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Intercrop; Silage; Mid-lactation